Hematopoietic cell transplant outcomes after myeloablative conditioning with fludarabine, busulfan, low‐dose total body irradiation, and rabbit antithymocyte globulin. Issue 9 (4th July 2020) - Ousia, Samar; Kalra, Amit; Williamson, Tyler S.; Prokopishyn, Nicole; Dharmani‐Khan, Poonam; Khan, Faisal M.; Jimenez‐Zepeda, Victor; Jamani, Kareem; Duggan, Peter R.; Daly, Andrew; Russell, James A.; Storek, Jan
Abstract: Optimal conditioning and graft‐vs‐host disease (GVHD) prophylaxis for hematopoietic cell transplantation (HCT) are unknown. Here, we report on outcomes after low toxicity, myeloablative conditioning consisting of fludarabine, busulfan, and 4 Gy total body irradiation, in combination with thymoglobulin and post‐transplant methotrexate and cyclosporine. We retrospectively studied 700 patients with hematologic malignancies who received blood stem cells from 7 to 8/8 HLA‐matched unrelated or related donors. Median follow‐up of surviving patients was 5 years. At 5 years, overall survival (OS), relapse‐free survival (RFS), and chronic GVHD/relapse‐free survival (cGRFS) were 58%, 55%, and 40%. Risk factors for poor OS, RFS, and cGRFS were (1). high to very high disease risk index (DRI), (2). high recipient age, and (3). cytomegalovirus (CMV)‐seropositive recipient with seronegative donor (D−R+). The latter risk factor applied particularly to patients with lymphoid malignancies. Neither donor other than HLA‐matched sibling (7‐8/8 unrelated) nor one HLA allele mismatch was risk factors for poor OS, RFS, or cGRFS. In conclusion, the above regimen results in excellent long‐term outcomes. The outcomes are negatively impacted by older age, high or very high DRI, and CMV D−R+ serostatus, but not by donor unrelatedness or one HLA allele mismatch.